Analysis Of The Effect Of Bi Rate Interest Rate Policy On Liquidity Performance Of Plantation Companies (Study At PTPN 4) - Didi Firmansyah; Dewi Maharani; Lia Nazliana (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2026)
The purpose of this study is to analyze the BI rate, inflation, and debt to equity ratio have a significant effect simultaneously on the current ratio and how the exchange rate, inflation, and current ratio have a significant effect simultaneously on the debt to equity ratio. This study uses time series data from 2009-2023 sourced from World Bank data, Bank Indonesia, and the annual report of PT. Perkebunan Nusantara with the simultaneous equation method and the Two Stage Least Square (TSLS) estimation technique. The results of the study found that in equation 1 (one) the BI rate, inflation, and debt to equity ratio variables do not have a significant effect on the current ratio of PT. Perkebunan Nusantara IV (Persero). In equation 2 (two) the exchange rate and inflation variables have a significant effect on the debt to equity ratio of PT. Perkebunan Nusantara IV (Persero). While the current ratio variable does not have a significant effect on the debt to equity ratio of PT. Perkebunan Nusantara IV (Persero).